Pengaruh Fungsi Manajemen Dan Kepuasan Kerja Terhadap Kinerja Pegawai RSUD Lamaddukkelleng Kabupaten Wajo - Hendra, Baso; Sibali, Alwi (LPPM STIE Tri Dharma Nusantara - Makassar, 2024)
This research aims to examine the influence of management functions, job satisfaction on the performance of employees at Lamaddukkelleng Hospital, Wajo Regency, as many as 125 people using the correlation analysis method and t test. This research found that there is a positive and significant influence of management functions and job satisfaction. The greatest correlation occurs between employee performance and management function at 0.834, while employee performance and job satisfaction also have a positive correlation at 0.702, This means that the management function and job satisfaction in the organization influence employee life behavior, attitudes, actions and thinking which leads to increased performance.